Popular Viennese Electronic Music, 1990-2015 A Cultural History - Mazierska, Ewa (Taylor & Francis, 2018)
Mazierska presents a cultural history of popular Viennese electronic music from 1990 to 2015, from the perspectives of production, scene and national and international reception. To illustrate this history in depth, a number of case studies of the most successful and distinguished musicians are explored, such as Kruder and Dorfmeister, Patrick Pulsinger, Tosca, Electric Indigo and Sofa Surfers. The author draws on research about electronic music, the relationship between music and the urban environment, the history of Austria and Vienna, music scenes and fandom, the digital shift , stardom in popular music (especially electronic music), as well as theories of postmodernism.